New technology for interactive CAL: the Origami project - Robert Harding; Steve Lay; Peter Robinson; Dan Sheppard; Richard Watts (Association for Learning Technology, 1997)
For many years, almost since the dawn of computing, people have speculated about the paperless society. Each new technology is heralded as the one that will finally take us to the fully electronic Utopia. However, the use of computers as document preparation tools has actually increased the number of paper documents. The latest mass-market development, the Internet, is unlikely to buck this trend even though the tools used seem to encourage on-screen browsing. The problems inherent with screen presentation have not gone away, while the amount of information available to the average computer user is increasing all the time.